A study of the adequacy of primary teacher training institutions in West Pakistan for effective teacher training - Qayyum, Abdul 1932- (s.n.], 1963)
This paper presents an appraisal of the primary teacher training institutions in West Pakistan and some offered practicable suggestions in improving the quality of training in the light of the practices in other countries, particularly the countries in Asia where the conditions happen to be similar to those in West Pakistan.